Military psychology or psychologies of militarism? The complexities of psychological research, training and intervention in Africa - Edlmann, Theresa (PINS-Psychology in Society, 2017)
[BOOK REVIEW] Van Dyk, Gideon, A J (ed) (2016) Military psychology for Africa. Stellenbosch: SUN Press. ISBN 978-1-920689-95-7 pbk. Pages x + 479 One of the longest and most complex themes of human existence is the personal, relational and environmental impacts of warfare. From ancient myths and rituals to contemporary theatres of conflict, military leaders, soldiers themselves, and all those with whom they share their lives inevitably grapple with the intensity of the battlefield, the scale of personal and systematic violence required, and the moral demands and contradictions of military life. Warfare in Africa has been particularly complex, given the roles of historical phenomena such as colonialism (and related issues like slavery, mining operations and the Cold War), and the contemporary nature of African conflicts and peacekeeping initiatives.